SINODALITAS GEREJA DAN PEMAHAMAN TENTANG GENDER : KAJIAN PERSPEKTIF ENSIKLIK MULIERIS DIGNITATEM DI PAROKI SANTO ANTONIUS PADUA SASI KEFAMENANU-NTT - Yata Mones, Anselmus; Maria Andika Feka (Sepakat : Jurnal Pastoral Kateketik, 2025)
Women continue to be victims of domestic violence, sexual harassment, and other forms of gender-based violence in various places. This research aims to deeply understand the synodality of the Church in shaping the congregation's understanding of gender. The meaning of synodality is closely related to the mission or service of the Church, which also involves women, thus requiring principles to further shape the understanding of gender from the perspective of Mulieris Dignitatem. The method used in this research is a qualitative descriptive method where the tools used for data collection are observation and interviews. The research results show that the community's understanding of gender is still limited to the equality of men and women. Understanding how to honor women as partners in God's creation and act like God in holiness has not yet been fully realized in real life. All congregants must comprehend gender understanding in the Church to prevent discrimination that can cause women to feel marginalized and perceive themselves as a weak, small, alienated, and useless group. However, on the contrary, women must always be taken into account, especially their role in responding to God's work of salvation. Synodality becomes a bridge to understanding gender and a key to further understanding gender in the perspective of Mulieris Dignitatem.